Ethnopragmatic Storytelling in Secondary Education: A Qualitative Analysis of Educators' Narrative Techniques in Denpasar City - Kadek Adyatna Wedananta; Anak Agung Adi Wiryya Putra (Journal of Psychology and Instruction, 2025)
This qualitative study investigates the utilization of ethnopragmatic storytelling methodologies by secondary educators in Denpasar City, Indonesia. This research utilizes an ethnopragmatic framework to examine the use of storytelling as an educational method by five teachers from two selected high schools, with the objective of imparting curriculum content while preserving cultural values and enhancing student engagement. This study employs in-depth semi-structured interviews and thematic analysis to delineate three primary themes: (1) cultural preservation through narrative pedagogy, (2) enhanced student engagement and comprehension, and (3) challenges in implementation and assessment. The findings demonstrate that ethnopragmatic storytelling successfully integrates local cultural knowledge with formal educational objectives, although educators face challenges in systematic implementation and evaluation. This study contributes to the growing literature on culturally responsive teaching and provides valuable guidance for high school educators seeking to implement narrative techniques.